2022
DOI: 10.1007/s41669-022-00328-4
|View full text |Cite|
|
Sign up to set email alerts
|

Implications of Payment for Acute Myocardial Infarctions as a 90-Day Bundled Single Episode of Care: A Cost of Illness Analysis

Abstract: Objectives Evaluate the cost of illness associated with the 90-day period following acute myocardial infarction (AMI) and the implication of care pathway (percutaneous coronary intervention [PCI] vs medical management [MM]), in order to assess the potential financial risk incurred by providers for AMI as an episode of care. Perspective Reimbursement payment systems for acute care episodes are shifting from 30-day to 90-day bundled payment models. Since follow-up care and readmissions beyond the early days/wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 34 publications
(42 reference statements)
0
5
0
Order By: Relevance
“…1 , 10 Consequently, cardiac readmission rates remain high and result in substantial costs. A major driver of these costs is hospitalization expenditure 11 , 12 with the average cost of a 30-day readmission postacute myocardial infarction (AMI) costing approximately USD $15,000, with a cumulative cost of over USD $1 billion per year. 13 …”
mentioning
confidence: 99%
“…1 , 10 Consequently, cardiac readmission rates remain high and result in substantial costs. A major driver of these costs is hospitalization expenditure 11 , 12 with the average cost of a 30-day readmission postacute myocardial infarction (AMI) costing approximately USD $15,000, with a cumulative cost of over USD $1 billion per year. 13 …”
mentioning
confidence: 99%
“…8,9,[34][35][36][37] In contrast, for cardiovascular care, PAC contributes less to variation in episode spending, and hospitalizations, which are less amenable to spending reductions, contribute more. 9,10,32,37,38 Furthermore, each cardiac bundle covers hospitalizations that range from elective admissions to life-threatening decompensations. This heterogeneity could lead to substantial variation in within-bundle care processes that resists "one-size-fits-all" efforts to reduce spending, such as blanket decreases in PAC use.…”
Section: Discussionmentioning
confidence: 99%
“… 8 , 9 , 34 37 In contrast, for cardiovascular care, PAC contributes less to variation in episode spending, and hospitalizations, which are less amenable to spending reductions, contribute more. 9 , 10 , 32 , 37 , 38 …”
Section: Discussionmentioning
confidence: 99%
“…Lastly, healthcare cost expenditures associated with various transition states and postoperative complications were derived from published reports ( Table E4 ). 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 To adjust for inflation, the Consumer Price Index was used to convert the obtained cost values into August 2023 United States Dollar amounts before model entry. More information regarding the literature sources used for deriving input parameters for both baseline and sensitivity analysis can be found in Table E5 , Table E6 , Table E7 , Table E8 , Table E9 .…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the study reported hospital charges, which may not reflect the total costs associated with an episode of transient ischemic attack. Allen et al E27 Description This study investigated costs of illness in the 90-d period after acute myocardial infarctions from 2015 to 2016 in 96,546 patients using Centers for Medicare & Medicaid Services standard analytical files. Strengths/applicability The study used multicenter data and had a large sample size, offering relatively substantial external validity.…”
Section: Appendix E1mentioning
confidence: 99%